Sinar Craft / Shah Imran Rosalie... [et al.] - Rosalie, Shah Imran; Mad Noh, Mohd. Shafiq Ruzaini; Ramu, Muhammad Noorizam; Kamel, Abdul Fatha; Azmar, Muhammad Ikmal Zyman (2012)
The name of our company is Sinar Craft. Sinar Craft business activity is landscape decoration which is to provide a modern contemporary design to decorate landscape in door and out door to give a property a look of class with our decorative stone items. We will open our factory to produce these items in Central Road, Off Tan Sri Ong Kee Hui Road, 93300 Kuching, Malaysia as a starting point and will develop in time in other regions in Malaysia and Internationally. This business had been created on the form of five partners and each partner has contributed an amount of capital equally as agreed in our agreement. All partners are responsible and encourage to participate in all business management and making sure our business is profitable with high quality products. We have agreed that Shah Imran Bin Rosalie as the General Manager, Mohd Shatiq Ruzaini Bin Mad Noh as the Marketing Manager, Abdul Fatha Bin Kamel as the Administration IManaoer, Muhammad Noorizam Bin Ramli as the Operation IVIanager and Muhammad Ikmal Zyman Bin Azmar as the Financial Manager. The top management is lead by the General Manager, whom is responsible for the planning leading, organizing and controlling of the business activities. Moreover, the General Manager IS responsible for the purpose of the business, its background, its partner background and the business background. The General Manager oversees the four main managers of the organization, which are divided into Marketing Manager, Administration Manager, Operation Manager, Financial Manager. The Marketing Manager is responsible to setting the marketing objectives, determining the product, identifying target market, analyzing the market trend sue, the competition, forecasting the sales, planning for the marketing employees, preparing the marketing budget, the market share, and developing strategies for the sales and promotion of the business.